Graduate employability and competence development in Higher Education: a systematic literature review using PRISMA - Abelha, Marta (2020)
This paper aims to develop a systematic review on graduate employability and competence development, intending to present an international perspective on the matter. It analyses the role of higher education institutions in promoting the development of competences for employability. The Preferred Reporting Items for Systematic Reviews (PRISMA) statement was used as a formal systematic review guideline for data collection. Data was obtained from research studies over the period 2009–2019. The analysis included a total of 69 papers from Web of Science (WoS) and Scopus databases. Results show that Europe leads the number of publications on these topics during the past decade. One of the main issues associated with competence development and graduate employability found in the review is related to the (mis)match between university graduates’ competences and employers’ needs. Findings indicate that higher education institutions are concerned with using strategies to enhance the development of competences for graduate employability. Graduate employability and competence development around the world depend on a strong sense of innovation and collaboration practices implemented in higher education.